A Comparative Study to Evaluate the Effect of Vaginal pH on Cervical Ripening with Dinoprostone Gel between Rural and Urban Prime Gravid Patients: An Hospital Based Study - Arun Kumar Chauhan; Divya Chaudhary (Asian Journal of Medical Research, 2020)
Background: Vaginal pH change also has a role in preterm delivery which suggests that it has a role in influencing cervical ripening. The aim of this study to evaluated the effect of vaginal pH on cervical ripening with dinoprostone (PGE2) gel between rural and urban primegravida.Subjects and Methods:This is hospital based comparative study done on 50 pregnant women admitted in labour room for induction of labour and fulfilling inclusion/exclusion criteria at Obstetrics and gynaecology department, RNT Medical college, Udaipur. Group I included patients with vaginal pH <4.5 and Group II included vaginal pH>4.5. A vaginal examination was then performed to determine the Bishop's score. After ruling out all contraindications Dinoprostone gel was applied endocervically.Results:Our study showed that mean age of pregnant women was 25.10 yrs in rural patients and 24.56 yrs in urban patients. The high vaginal pH (>4.5) was more in urban pregnant women as compare to rural pregnant women, it was statistically non-significant (P=0.1062) and low vaginal pH (?4.5) was more in rural as compare to urban. The augmentation required, time to active labor & time to induction delivery interval was not statistically significant (P=0.4276, P=0.2341 & P=0.1445 respectively) in between rural & urban pregnant women. LSCS was more common in rural as compare to urban pregnant women, but did not statistically significant (P=0.1945 NS).Conclusion: We concluded that higher vaginal pH more often responds to a single induction and is more often associated with vaginal deliveries rather than non-progress of labor.